Cooling of in vitro-produced bovine embryos: Effects of medium and time on gene expression, DNA fragmentation and embryonic survival - Marqui, Fernanda N. [UNESP]; Martins, Alicio [UNESP]; Cardoso, Tereza C. [UNESP]; Cruz, Tairini E. [UNESP]; Dell'Aqua, José Antônio [UNESP]; Oba, Eunice [UNESP] (Elsevier, 2019)
The aim of this study was to investigate the effects of Medium 199 (M199) and BotuEmbryo® (BE) as well as the time (24 an 48 h) of cooling at 5 °C on the transcript level of genes related to bovine embryonic metabolism (GLUT1) and cellular stress (HSPA1A, PRDX1 and SOD1), on the rate of blastocyst re-expansion and hatch, embryo survival, total number of cells and DNA fragmentation in IVP bovine embryos. There was an overall reduction in embryo survival and development to hatching/hatched stage with the increase in cooling time, especially in those cooled in M199. Although TUNEL-positive cells were identified in both cooled and NC embryos, a higher number of apoptotic cells was observed in BE-48 than in NC and BE-24. However, no effect of either medium or cooling time was found among all groups for the set of gene transcripts. In conclusion, no detrimental effect on the expression of genes as well as embryonic cell proliferation was remarkable in cooling of IVP bovine embryos. However, according to the in vitro predictive assessment of embryo viability, the cooling of IVP bovine embryos in the evaluated media appears to be feasible for 24 h but not for 48 h.
Keywords: Apoptosis; BotuEmbryo®; Hypothermic preservation; Medium 199; qPCR